Family visitation policies, facilities, and support in Australia and New Zealand intensive care units: A multicentre, registry-linked survey. Issue 4 (July 2022) - Tabah, Alexis; Ramanan, Mahesh; Bailey, Rachel L.; Chavan, Shaila; Baker, Stuart; Huckson, Sue; Pilcher, David; Litton, Edward
Abstract: Objective: The objective of this study was to describe family visitation policies, facilities, and support in Australia and New Zealand (ANZ ) intensive care units (ICUs). Methods: A survey was distributed to all Australian and New Zealand ICUs reporting to the Australian and New Zealand Intensive Care Society Centre for Outcomes and Resources Evaluation Critical Care Resources (CCR) Registry in 2018. Data were obtained from the survey and from data reported to the CCR Registry. For this study, open visiting (OV) was defined as allowing visitors for more than 14 h per day. Setting and participants: This study included all Australian and New Zealand ICUs reporting to CCR in 2018. Main outcome measures: The main outcome measures were family access to the ICU and visiting hours, characteristics of the ICU waiting area, and information provided to and collected from the relatives. Findings: Fifty-six percent (95/170) of ICUs contributing to CCR responded, representing 44% of ANZ ICUs and a range of rural, metropolitan, tertiary, and private ICUs. Visiting hours ranged from 1.5 to 24 h per day, with 68 (72%) respondent ICUs reporting an OV policy, of which 64 (67%) ICUs were open to visitors 24 h a day. A waiting room was part of the ICU for 77 (81%) respondent ICUs, 74 (78%) reported a separate dedicated room for family meetings, and 83 (87%) reported available social worker services. Most ICUs reported facilities for sleeping within or near the hospital. An information booklet was provided by 64 (67%) ICUs. Only six (6%) ICUs required personal protective equipment for all visitors, and 76 (80%) required personal protective equipment for patients with airborne precautions. Conclusions: In 2018, the majority of ANZ ICUs reported liberal visiting policies, with substantial facilities and family support.